ANTIFUNGAL ACTIVITY OF ACTINOBACTERIA WITH A POTENTIAL TO INHIBIT RICE BLAST FUNGUS MAGNAPORTHE ORYZAE (ANAMORPH PYRICULARIA ORYZAE) - R, THILAGAM; R, BALAGURUNATHAN; M, SANGEETHA; N, HEMALATHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aims of the present study were to screen the actinobacteria with high potential ability to produce secondary metabolites that have inhibitory activity against plant pathogenic fungi, Magnaporthe oryzae. Production of secondary metabolites was analysis by thin-layer chromatography and bioautography assay. Methods: Screening and selection of potential Streptomyces sp. morphological, cultural, physiological, and biochemical characterization of the screened isolate was carried out. Antifungal compound was confirmed by bioautography assay. Results: Bioautography method use in this study was found to be antifungal fraction from the crude extract. Antifungal secondary metabolites can be readily located on the plates by observing clear zones where active compounds inhibit fungal growth. Conclusion: The bioautography assay shows that this isolates can produce antifungal compound. Therefore, this isolate proves to be a promising microbe which can be further studied for its applications a biocontrol agent against rice blast fungi.